Tumor-targeted IL-12 combined with tumor resection yields a survival-favorable immune profile. Issue 1 (17th June 2019) - Zhao, Qingnan; Hu, Jiemiao; Mitra, Abhisek; Cutrera, Jeffry; Zhang, Wendong; Zhang, Zhongting; Yan, Jun; Xia, Xueqing; Mahadeo, Kris Michael; Livingston, John Andrew; Gorlick, Richard; Li, Shulin
Abstract : Background: Although accumulated evidence provides a strong scientific premise for using immune profiles to predict survival in patients with cancer, a universal immune profile across tumor types is still lacking, and how to achieve a survival-associated immune profile remains to be evaluated. Methods: We analyzed datasets from The Cancer Genome Atlas to identify an immune profile associated with prolonged overall survival in multiple tumor types and tested the efficacy of tumor cell-surface vimentin–targeted interleukin 12 (ttIL-12) in inducing that immune profile and prolonging survival in both mouse and patient-derived xenograft tumor models. Results: We identified an immune profile (IFNγ Hi CD8 Hi FOXP3 Low CD33 Low ) associated with prolonged overall survival across several human tumor types. ttIL-12 in combination with surgical resection of the primary tumor transformed tumors to this immune profile. Intriguingly, this immune profile transformation led to inhibition of metastasis and to prolonged survival in both mouse and patient-derived xenograft malignant models. Wild-type IL-12 combined with surgery was significantly less effective. In the IL-12–sensitive C3H mouse strain, in fact, wild-type IL-12 and surgery resulted in shorter overall survival than in mice treated with control pDNA; this surprising result is believed to be attributable to IL-12 toxicity, which was absent in the mice treated with ttIL-12. The ttIL-12–induced immune profile associated with longer overall survival was also associated with a greater accumulation of CD8 + T cells and reduced infiltration of regulatory T cells, myeloid-derived suppressor cells, and tumor-associated macrophages. The underlying mechanism for this transformation by ttIL-12 treatment was induction of expression of CXCL9 and reduction of expression of CXCL2 and CCL22 in tumors. Conclusions: ttIL-12 when combined with surgery led to conversion to the IFNγ Hi CD8 Hi FOXP3 Low CD33 Low immune profile, eliminated relapse and metastasis, and prolonged overall survival.